APAKAH GERAK TANGAN DAN TUBUH SELARAS DENGAN UNGKAPAN EMOSI YANG TERLIHAT DI WAJAH - Prawitasari, Johana E (Jurnal Psikologi, 1997)
It is faith that humans are not able to live alone. They need somebody else to take care of them from birth to death. To communicate their needs, they need some tools. When they are still babies they use simple nonverbal communication, such as bubbling, crying, cooing, gesturing to indicate their needs. Growing older,Â  they use the same language with people in their communications.